EVALUASI KELAYAKAN USAHA INDUSTRI RUMAH TANGGA: EVALUATION OF THE FEASIBILITY OF A HOME INDUSTRY - Dede Erni Nurasia; Ida Marina (Journal of Innovation and Research in Agriculture, 2023)
Mango is one of the fruits that has a good opportunity in agriculture, beside can be consumed directy also can be consumed in prosessed one. Seeing that potential, home industry that selle mango stick has a good value-added. The purpose of the research is to evaluate the feasibility both financially and non financially on Rossya’s stick mango. The method that’s used in the research is quantitative descriptive by analysing feasibility in business non financially with the criteria in law aspect, environment aspect, human resources aspect, market and marketing aspect, technical and technology aspect, financial feasibility with R/C and B/C as the criteria. The research result shows that the home industry stick mango is worthy to be developed reviewed by feasibility non financial although it hasn’t have fulfill law aspect, which is doesn’t have permission. In terms of fianancial with criteria R/C of 2,16 so that R/C 2,16 > 1, B/C of 1,16 so that 1,16 > 1.